Application of Agricultural Waste-Based Fermented Feed to Increase the Daily Weight of Etawa Crossbred Goats (PE) - Marpaung, Suhendra Marningot; Timotius Simangunsong (Cattleya Darmaya Fortuna, 2025)
Agricultural waste (rice bran, ground corn cobs, coffee husks) has the potential to become economical feed after fermentation to increase digestibility and nutrient availability. This study evaluated the effect of fermented feed based on agricultural waste on daily weight gain (ADG), feed consumption, feed conversion ratio (FCR), and health status of Etawa crossbred (PE) goats. A completely randomized design was used with four treatments: T0 (control—basal feed), T1 (10% fermentation), T2 (20%), T3 (30%) of the total dry ration; each with 8 replications, a 14-day adaptation period, and a 56-day maintenance period. Fermentation used Lactobacillus sp. + yeast (1–2% inoculum), 3–5% molasses, 60–65% water content, and 7 days of anaerobic incubation. Main variables: ADG (g/head/day), DM intake (g/day), FCR = DM intake / body weight gain, in vivo digestibility (DM/BO), blood profile (Hb, hematocrit), and NDF/ADF feed. Expected results: T2–T3 increased ADG and decreased FCR compared to control (p<0.05) without compromising health. The study confirms fermented agricultural waste feed as a low-cost, high-impact option for improving PE goat performance and waste management.